Mental health symptoms in relation to socio-economic conditions and lifestyle factors - a population-based study in Sweden - Persson Carina; Nordström Eva; Lindén-Boström Margareta; Eriksson Hans G; Eriksson Charli; Berglund Kenneth; Molarius Anu; Sahlqvist Lotta; Starrin Bengt; Ydreborg Berit (BMC, 2009)
Abstract Background Poor mental health has large social and economic consequences both for the individual and society. In Sweden, the prevalence of mental health symptoms has increased since the beginning of the 1990s. There is a need for a better understanding of the area for planning preventive activities and health care. Methods The study is based on a postal survey questionnaire sent to a random sample of men and women aged 18-84 years in 2004. The overall response rate was 64%. The area investigated covers 55 municipalities with about one million inhabitants in central part of Sweden. The study population includes 42,448 respondents. Mental health was measured with self-reported symptoms of anxiety/depression (EQ-5D, 5th question). The association between socio-economic conditions, lifestyle factors and mental health symptoms was investigated using multivariate multinomial logistic regression models. Results About 40% of women and 30% of men reported that they were moderately or extremely anxious or depressed. Younger subjects reported poorer mental health than older subjects, the best mental health was found at ages 65-74 years. Factors that were strongly and independently related to mental health symptoms were poor social support, experiences of being belittled, employment status (receiving a disability pension and unemployment), economic hardship, critical life events, and functional disability. A strong association was also found between how burdensome domestic work was experienced and anxiety/depression. This was true for both men and women. Educational level was not associated with mental health symptoms. Of lifestyle factors, physical inactivity, underweight and risk consumption of alcohol were independently associated with mental health symptoms. Conclusion Our results support the notion that a ground for good mental health includes balance in social relations, in domestic work and in employment as well as in personal economy both among men and women. In addition, physical inactivity, underweight and risk consumption of alcohol are associated with mental health symptoms independent of socio-economic factors.